2009
DOI: 10.1177/0034355208323947
|View full text |Cite
|
Sign up to set email alerts
|

Unifying and Elevating Rehabilitation Counseling Through Model-Driven, Diversity-Sensitive Evidence-Based Practice

Abstract: Rehabilitation counseling must embrace an evidence-based practice paradigm to remain a vital and respected member of the future community of professions in rehabilitation and mental health care and to fully discharge its responsibility to assist consumers in accessing effective rehabilitation interventions and exercising truly informed choice. The goals of this article are to (a) discuss the importance of using model-driven and culturally sensitive evidence-based rehabilitation counseling practices to enhance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
57
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 13 publications
0
57
0
Order By: Relevance
“…The EBP framework advocates that rehabilitation professionals deliver clinical practices that are based on the strongest scientific evidence (Chan, Tarvydas, Blalock, Strauser, & Atkins, 2009). Furthermore, the use of EBP enables counselors to fulfill their ethical obligations to consumers by better protecting consumers from harm pool from which they adopt new practices.…”
Section: Introductionmentioning
confidence: 99%
“…The EBP framework advocates that rehabilitation professionals deliver clinical practices that are based on the strongest scientific evidence (Chan, Tarvydas, Blalock, Strauser, & Atkins, 2009). Furthermore, the use of EBP enables counselors to fulfill their ethical obligations to consumers by better protecting consumers from harm pool from which they adopt new practices.…”
Section: Introductionmentioning
confidence: 99%
“…The field of rehabilitation places a strong emphasis on the use of empirically-validated, practical and effective tools to assess psychosocial adjustment to disability and well-being [54]. In research and in clinical practice, the ultimate goal of using these assessments is to identify traits that contribute to positive rehabilitation outcomes and then to enhance and/or capitalize on these traits via evidence-based practice.…”
Section: Implications For Research and Practicementioning
confidence: 99%
“…Evidence-based practice advocates that rehabilitation professionals should have an interest in delivering the best possible services to their consumers, based whenever possible on the best clinical practices available from the research evidence (Chan, Tarvydas, Blalock, Strauser, & Atkins, 2009). Leahy et al (2009) suggested that the emphasis of VR in the future will be on the meaning of research findings to practitioners and consumers in improving services, interventions, and employment outcomes for persons with disabilities, and translating and disseminating EBP that come from research efforts to the level of the organization that will affect and inform practice and policy.…”
Section: Introductionmentioning
confidence: 99%
“…The development of theory-driven or model-driven research to inform best practices in rehabilitation will undoubtedly be highly important as professionals in the field strive to improve the effectiveness of VR services and outcomes, especially for subpopulations of VR consumers with the poorest rehabilitation outcomes (Chan et al, 2009). In this special issue, we reported the findings of the four-state multiple case study (Maryland, Mississippi, Texas, and Utah) conducted by researchers at the Rehabilitation Research and Training Center for Evidence-Based Practice in Vocational Rehabilitation (RRTC-EBP VR) to identify evidence-based best VR practices, as well as organizational and cultural factors promoting best practices in the public vocational rehabilitation program.…”
Section: Introductionmentioning
confidence: 99%